2016
DOI: 10.13189/ijnbs.2016.040101
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Neglect: Assessment and Rehabilitation

Abstract: Over 795,000 individuals in the U.S. suffer from strokes annually, with 610,000 accounting for first attacks. Stroke represents the fifth leading cause of death and resulting long-term disability in the United States. Unilateral neglect (UN) is a disabling characteristic of stroke, occurring from lesion damage to one hemisphere of the brain. Individuals with UN do not respond normally to objects, stimuli, and people located to their contralesional side. Right hemispheric lesions exhibit the greatest impairment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
3
0
1
Order By: Relevance
“…Unilateral spatial neglect (USN) is a common disabling condition following right brain damage, is typically characterized by a failure to respond to stimuli and realize on the contralateral side and unable to use extremities opposite the lesion [1][2][3] . This neglect condition caused impaired mobility, decreased long-term functional outcomes, limited ability to complete daily activities, and restricted social participation 4,5) . Various training modalities and therapeutic interventions have been devel-oped to overcome complex USN problems 6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral spatial neglect (USN) is a common disabling condition following right brain damage, is typically characterized by a failure to respond to stimuli and realize on the contralateral side and unable to use extremities opposite the lesion [1][2][3] . This neglect condition caused impaired mobility, decreased long-term functional outcomes, limited ability to complete daily activities, and restricted social participation 4,5) . Various training modalities and therapeutic interventions have been devel-oped to overcome complex USN problems 6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral spatial neglect is a lateralised attention disorder characterised by the failure to orient to, attend to, respond to, or report stimuli appearing on the contralesional hemispace (Buxbaum et al, 2004; Vuilleumier, 2013), despite having intact sensory abilities (Howard & Rowe, 2018). It is commonplace, long-lasting, but highly variable following stroke (Kaufmann, Cazzoli, Muri, Nef, & Nyffeler, 2020a; Kaufmann et al, 2020b; Harvey, Learmonth, Rossit, & Chen, 2021; Ringman, Saver, Woolson, Clarke, & Adams, 2004) and results in long-term major disability (Checketts et al, 2020; Conti & Amone, 2016; Wee & Hopman, 2008). Lateralised frontoparietal neuroanatomical networks, especially in the right hemisphere, are strongly implicated in the pathology (He et al, 2007; Pedrazzini & Ptak, 2020; Wu et al, 2016).…”
Section: Neglect Results In Long-term Cognitive Disabilitymentioning
confidence: 99%
“…Rehabilitation methods for LHSN associated symptoms were extensively investigated in persons with right cerebral stroke (4)(5)(6)(7)(8). Previous studies showed the efficacy of 1 Hz inhibitory repetitive Transcranial Magnetic Stimulation (i-rTMS) on visuospatial symptoms in persons with an ischemic lesion of the right hemisphere.…”
Section: Introductionmentioning
confidence: 99%